Phylogenetics of tropical butterflies (Family: Nymphalidae) in the rain forests of Sabah, Malaysia - Nazirah Mustaffa (2005)
This study examined phylogenetics of the butterflies genus Mycalesis and cryptic species of the genera Euthalia and Tanaecia. The study sites consisted of ten lowland rain forest resetves in Sabah Borneo. Baited traps and hand-netting techniques were used in butterfly sampling. In this study, mitochondrial DNA COIi gene was used to infer phylogenetic relationships of the study groups. In the study of Mycalesis, 396 base pairs of DNA sequences were obtained from 42 individuals representing 13 species. The analyses of phylogenetic relationship revealed that the species formed four major clades, which were supported by high similarities in morphological characteristics based on male genitalia and wing colour patterns. The species that appeared as a basal taxon to its clade has wider geographical distribution compared with the other members of the c/ade. The analysis of ecological traits showed that species evolution of Mycalesis follows the gradual evolution patterns, of which the species evolution progressed with time. In the study of cryptic species of the genera Euthalia and Tanaecia, 416 base pairs of DNA sequences were obtained from 34 individuals, comprising of five species of the genus Euthalia and five species of the genus Tanaecia.. The phylogenetic analyses showed that the genus Euthalia is paraphyletic to Tanaecia. The level of genetic divergence is relatively low in Tanaecia species compared with Euthalia. Two of the Euthalia species, E iapis and E godarti appeared as a monophyletic group to the Tanaecia species. The results suggest that £ iapis and E godarti should belong to the Tanaecia group rather than Euthalia. In contrast, E iapis and E godarti possessed genitalia and wing characteristics highly similar with the other species of Euthalia. By using male individuals in the phylogenetic analyses, relationships of the two genera were better resolved. The results reflected the unreliability of species identification based on female morphological characteristics. The phylogenetic information of Mycalesis and the genera Euthalia and Tanaecia were applied in the investigation of the use of phylogenetic diversity in forest reserve conservation in Sabah. Results showed no pattern on relationships between the phylogenetic diversity of the two study groups. Relationships of the phylogenetic diversity of Mycalesis and some other parameters which were species number of Mycalesis sampled, total number of species sampled, Shannon-Wiener diversity index and the size of the reserves were included in this study. The results showed that the phylogenetic diversity of Mycalesis was positively correlated with number of species of Mycalesis sampled, and the number of Mycalesis species was positively correlated with the reserve sizes. This findings suggest that habitat sizes is important in conserving vulnerable species, as many Mycalesis species and thus, is important in conserving phylogenetic diversity. However, caution must be taken when interpreting the results because this study was based on limited range of species, and undoubtedly, more studies are needed to support the proposed conclusions.